A Critical Study of Transportation Cost in Inland Road Transportation Business - Kerot, Thanatorn; Deesamer, Kornkanok; Sanonok, Arisa; Baobuangoen, Jidapa; Pornsing, Choosak (Naresuan University Journal: Science and Technology (NUJST), 2021)
This research aimed to study the Critical of Transportation Cost in Inland Road Transportation Business, which is considered one of the industries that are important to drive the country's economy with a relatively high proportion of transportation as well as the proportion of costs in Freight. Thus, managing the cost of transportation to be most efficient will help enhance the capacity of the economy in this industrial sector to have more growth. This research started with a review of the secondary data. Then, the researcher conducted survey research on critical transportation costs in Truck Operators Certified Q-Mark from the Department of Land Transport (2018). Then, it comprehensively analyzes and synthesizes the guidelines for using modern technology to manage the real cost of road transportation. The results of the study revealed that the companies have the highest proportion of fuel costs, up to 33.70 %, and found that most establishments have adopted GPS technology to manage transportation costs the most, along with incentive measures to encourage employees to be aware and take part in saving fuel rates. Although enterprises are used to track and review fuel usage, corruption is still encountered. Due to the consistency analysis of fuel cost and transportation activities, the test statistics at 0.10 level, it found that most establishments with fuel costs were inconsistent with transportation activities, indicating that there is a corruption in fuel costs. Keywords:  Logistics, Transportation Cost Structure, Fuel Cost Management, Q-Mark Standard, Road Transportation, Driver   Behavior